2021
DOI: 10.1021/acsomega.1c01044
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Highly Leaching-Resistant Fire-Retardant Wood by In Situ Polymerization with Melamine Formaldehyde Resin

Abstract: The objective of the work was to improve the leaching resistance of fire-retardant (FR) modified wood by the incorporation of a thermoset resin. Here, Scots pine ( Pinus sylvestris L.) sapwood was impregnated with melamine formaldehyde (MF) resin and hydrophilic FRs guanyl-urea phosphate/boric acid by a vacuum-pressure treatment. Resistance to leaching of FR-modified wood was evaluated, after conducting an accelerated aging test according to European standard EN 84. Inductively coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…The chemical functionalities of the specimens analyzed by FTIR are shown in Figure 7. The spectrum of the unmodified wood was assigned to the typical wood components cellulose, hemicellulose, and lignin [28]. The bands in the region of 3000 to 2800 cm −1 originated from C-H aliphatic stretching of the wood (maxima at 2923 cm −1 and 2857 cm −1 ).…”
Section: Chemical Functionalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical functionalities of the specimens analyzed by FTIR are shown in Figure 7. The spectrum of the unmodified wood was assigned to the typical wood components cellulose, hemicellulose, and lignin [28]. The bands in the region of 3000 to 2800 cm −1 originated from C-H aliphatic stretching of the wood (maxima at 2923 cm −1 and 2857 cm −1 ).…”
Section: Chemical Functionalitiesmentioning
confidence: 99%
“…In the fire-retardant furfurylated wood products, 3-30FA and 5-30FA, a new band at 1667 cm −1 assigned to the C=O groups from GUP was found [28]. The band at 1714 cm −1 became less visible and was probably because triethanolamine saponified the acids and inhibited the hydrolytic opening of furan rings [40,53].…”
Section: Chemical Functionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The char nally ruptured, resulting that heat being released in large quantities, reaching P 2 HRR, and nally, the volatile products were consumed completely, leaving only debris and ash. The HRR curves showed that Control was burned quickly after ignition with a P The generation of smoke, including particulate matter and toxic gases in the re, is also a key parameter in assessing the ame retardancy properties of materials (Lin et al 2021). P 1 SPR of WPUC-7 was signi cantly smaller than that of WPUC-5 and WPUC-9, and the SPR of the second peak of WPUC-7 produced faster than the other samples, relating to the combustion of shavings and the formation of a carbon layer.…”
Section: Thermal and Thermo-oxidative Stability Of Wpucsmentioning
confidence: 99%
“…In general, filling the cell cavity with resin can improve both the strength and dimensional stability of the wood [ 27 , 28 ]. However, commonly used resins are aldehydes, such as phenolic (PF) [ 29 , 30 , 31 , 32 ], urea-formaldehyde (UF) [ 33 , 34 , 35 ] and melamine (MF) [ 36 , 37 , 38 , 39 ] resins. The slow release of formaldehyde, which in turn endangers the environment and human health, restricts the popularization and application of this type of technology.…”
Section: Introductionmentioning
confidence: 99%